PENGARUH TEKANAN SOSIAL TERHADAP KEPUASAN KERJA DENGAN LOCUS OF CONTROL (LOC) SEBAGAI VARIABEL MODERATING PADA PDAM SURYA SEMBADA KOTA SURABAYA - FILOSOFI SULTHON, MUQORROBIN (Jurnal Ilmu Manajemen (JIM), 2017)
A well managed organization does not see capital investment as a source of improvement, but sees employees as a basic resource of improvement. The persistence of this research is to know the influence of social pressure on job satisfaction with moderated locus of control at PDAM Surya Sembada Surabaya city. Employee PDAM Surya Sembada Surabaya city public relations division, marketing and customer service and human resources development is the object of research in this study. The samples used in this research were 60 employees in the three divisions obtained by using Two stage sampling method where the first stage selected the group as a sample by judgment sampling technique (purposive sampling) and the second stage using simple random sampling. This research uses quantitative approach obtained by observation, interview and spreading of questionnaire. Partial least square analysis method (PLS) is the analyst used in this study. The results of this study indicate that social pressure has a positive and substantial effect on employee job satisfaction in PDAM Surya Sembada Surabaya which means that if social pressure is high then job satisfaction is also high and vice versa. While the locus of control does not moderate the influence of social pressure on employee job satisfaction at PDAM Surya Sembada Surabaya. Keywords: Social pressure, Job satisfaction, locus of control